MAGNETIC SIGNATURE OF HEAVY METALS POLLUTION OF SEDIMENTS: CASE STUDY FROM THE EAST LAKE IN WUHAN, CHINA - Yang T.; Liu Q.; Chan L.; Liu Z. (My University, 2007)
Detailed magnetic measurements and geochemical analyses were performed on 114 sediment samples collected from the East Lake, Wuhan city, China, to establish a possible link between the enhanced concentration of anthropogenic magnetic particles and heavy metals with known sources. Relatively higher magnetic susceptibility values (mass-specific, χ, >150 × 10 -8 m3 kg-1) were observed for samples near the pollution sources: e.g. the Wuhan Iron and Steel Company (WISC), the Qingshan Thermal Power Plant (QTPP), the banks (driveways) of the lake and near the sightseeing route of yachts on the lake. Moreover, χ is positively correlated to the concentration of Pb (correlation coefficient r = 0.682), but negatively or weakly correlated with both Zn and Cu. In contrast, anhysteretic remanent magnetization (ARM) is significantly correlated with these major heavy metals (r = 0.645 for Zn-ARM, 0.699 for Pb-ARM and 0.841 for Cu-ARM, respectively), which indicate that ARM serves a better indicator for the pollution of heavy metals in this lake. Thermomagnetic analysis combined with magnetic hysteresis measurements revealed that magnetites in the pseudo-single-domain/multidomain grain-size regions are dominant. Scanning electron microscopy and energy dispersive X-ray examinations of the magnetic extracts showed that these Fe-rich particles have different morphologies: orange-peel structure, hollow structure with adhered smaller particles, Zr-rich melted-like irregular particles, pear-shaped spherules and spherules with slick surfaces. These features are typical for particles produced by anthropogenic activities. Because of the genetic relationship between the environmental setting of the East Lake and the nearby pollution sources, this study suggests that in situ magnetic surveys are sensitive to evaluate the environmental pollution on the lake bottom. © 2007 Springer-Verlag.
Keywords: EAST LAKE; HEAVY METALS; LAKE SEDIMENTS; MAGNETIC SUSCEPTIBILITY; POLLUTION; WUHAN CITY